Integrating System Dynamics Into Action Research: Drivers and Challenges in a Synergetic Complementarity; Comment on "Insights Gained From a Re-analysis of Five Improvement Cases in Healthcare Integrating System Dynamics Into Action Research" - Mohammadreza Zolfagharian (Kerman University of Medical Sciences, 2023)
This commentary discusses the paper by Holmström et al that explored how system dynamics (SD) may contribute effectively to an action research (AR) process to improve five health case studies. Accordingly, we reviewed some of the methodological aspects of the proposed integration of SD into AR using ongoing debates on multi-methodology and mixed methods research. In a systemic evaluation of the proposed design, we concentrated on some of the common distinct features of SD and AR, and the challenges as well as the expected outcomes of this integration. Finally, we tried to position the suggested framework within the multi-methodology efforts and to pave the way for developing it in future research and practice.